A Comparative Analysis of Partial Replacement of Yeast with CO2 Gas Hydrates as Leavening Agents in Baking of Wheat Bread - Srivastava, Shubhangi; Kollemparembil, Ann Mary; Zettel, Viktoria; Claßen, Timo; Mobarak, Mohammad Mobarak; Gatternig, Bernhard; Delgado, Antonio; Jekle, Mario; Hitzmann, Bernd (Processes, 2023)
The aim of this study is to examine how CO2 gas hydrates (CO2 GH) are used in baking, notably in the creation of wheat bread, as a leavening agent. CO2 GH were produced with the use of food grade amino acids called promoters. The article emphasizes an interesting approach by using a hybrid combination of yeast and CO2 GH. The current study is based on a comparative evaluation of leavening agents in bread with (1) GH with promoters (20–70% GH) and (2) GH with promoters + yeast as a partial replacement (25–75%). The results obtained are then also compared with those of standard yeast bread along with the effects on wheat bread quality parameters such as volume, specific volume, hardness, moisture content, baking loss, and pore size. The GH bread with promoters had baking losses that were equivalent to the quality of traditional yeast bread. The breads with 60% and 70% GH with promoters had the best outcomes when compared with standard yeast bread. When a combination of CO2 GH with promoters (20–70%) and yeast (25–75%) was used in the study, the best combinations were obtained with 70% GH + 50% yeast and 70% GH + 75% yeast. Additionally, this article clarifies some potential future uses for CO2 GH as leavening agents in the bread industry, with a discussion of potential limitations as well as the cost efficiency of the developed technology. This information could help in the creation of new methods and standards for better CO2 GH selection for usage in other bakery goods.
CRIS-Team Scopus Importer:2023-04-14
Keywords: amino acids; bread; CO; leavening; promoters; yeast

A Comparative Analysis of Partial Replacement of Yeast with CO2 Gas Hydrates as Leavening Agents in Baking of Wheat Bread - Srivastava, Shubhangi; Kollemparembil, Ann Mary; Zettel, Viktoria; Claßen, Timo; Mohammad, Mohammad Mobarak; Gatternig, Bernhard; Delgado, Antonio; Jekle, Mario; Hitzmann, Bernd (Processes, 2023)

An Innovative Approach in the Baking of Bread with CO2 Gas Hydrates as Leavening Agents - Srivastava, Shubhangi; Kollemparembil, Ann Mary; Zettel, Viktoria; Claßen, Timo; Mobarak, Mohammad Mobarak; Gatternig, Bernhard; Delgado, Antonio; Jekle, Mario; Hitzmann, Bernd (Foods, 2022)
Gas (guest) molecules are trapped in hydrogen-bonded water molecules to form gas hydrates (GH), non-stoichiometric solids that resemble ice. High pressure and low temperature are typical conditions for their development, with van der Waals forces joining the host and guest molecules. This article study investigates the application of CO2 gas hydrates (CO2 GH) as a leavening agent in baking, with particular reference to the production of wheat bread. The main intention of this study is to better understand the complex bread dough formed by CO2 GH and its impact on product quality. This may enable the adaptation of CO2 GH in baking applications, such as those that can specifically influence wheat bread properties, and so the final bread quality. The present research further examines the comparative evaluation of yeast bread with the GH bread’s impact on bread quality parameters. The amount of GH was varied from 10 to 60%/amount of flour for the GH breads. The GH breads were compared with the standard yeast bread for different quality parameters such as volume, texture, and pore analysis. The results show that the bread with 20% and 40% GH obtained the best results in terms of volume and pore size. Moreover, this article also sheds some light on the future applications of the use of CO2 GH as leavening agents in foods. This knowledge could help to create new procedures and criteria for improved GH selection for applications in bread making and other bakery or food products.
CRIS-Team Scopus Importer:2022-12-02
Keywords: bread; browning; CO; dough; food applications; leavening; leavening

CO2 gas hydrate as an innovative leavening agent for baked goods - Frühling, Yvonne; Claßen, Timo; Mobarak, Mohammad Mobarak; Bauer, Marius; Zettel, Viktoria; Gatternig, Bernhard; Hitzmann, Bernd; Delgado, Antonio (Future Foods, 2023)
In the presented research, the use and technical realization of CO2 gas hydrate (GH) as a novel baking agent is investigated. GH are ice-like structures where one mole of hydrate typically consists of about 85% water and 15% gas. Hydrates were formed in a lab-scale 1.1 L stirred tank reactor at 1-2 degrees C and 3.5 MPa, and transferred into a temperature-controlled, gas-tight measuring cell. The leavening effect of gas hydrates was assessed by measuring the CO2 release rates. Storage stability at-20 to 0 degrees C and stability above 0 degrees C were investigated experimentally and a coupled thermodynamic and kinetic decay model implemented. At-10 degrees C, gas release was highest in the first minutes and stopped completely after 5 days. After 21 days storage at-10 degrees C, the GH still contained 20 % of the initial gas content. Above 0 degrees C, dissociation rates were highly temperature dependent, and half value times ranged from 30 min (3 degrees C) to 4 min (20 -30 degrees C). Above 10 degrees C, ambient temperature had only a minor effect on the dissociation rates. Results from the kinetic decay model, applied for a 21 mm particle, showed similar dissociation behavior as a particle from experiments. Applying the model for a 3 mm particle, showed full dissociation after approximately 15 min. Stability and baking tests showed that CO2 hydrate is in principle suitable as a leavening agent. However, GH production still needs to be optimized and recipes for GH application require further development.
CRIS-Team WoS Importer:2023-04-14

Concentration of apple juice using CO(2 )gas hydrate technology to higher sugar contents - Claßen, Timo; Jäger, Michael; Loekman, Soebiakto; Gatternig, Bernhard; Rauh, Cornelia; Delgado, Antonio (Innovative Food Science & Emerging Technologies, 2020)
This paper describes the application of CO2-hydrate technology for the concentration of apple juice towards industrially relevant levels. Assays were carried out in a stirred autoclave at 1-2 degrees C and 35 bars with rediluted apple concentrate in the range of 11 degrees Bx to 40 degrees Bx. A hydraulic pellet press was used to separate the hydrate from the concentrate, resulting in an almost complete sugar recovery. It was found that apple juice can be concentrated to 45 degrees Bx and beyond using this technique. Maximum hydrate conversion of up to 30% was achieved at an average concentration rate of 2.5-3 degrees Bx/h. Furthermore, an optimal juice to crystallizer volume ratio of 35% was found. The investigations also revealed the juice composition to interfere with the hydrate formation process to some extend. In the assays with constant water content, no decrease in the hydrate formation rate was observed until 30 degrees Bx. From this concentration onwards, however, the hydrate yield decreased steadily and amounted to only 15% M 40 degrees Bx.
CRIS-Team WoS Importer:2020-09-25

Food technological potentials of CO2 gas hydrate technology for the concentration of selected juices - Seidl, Pia; Loekman, Soebiakto; Sardogan, Miray; Voigt, Erik; Claßen, Timo; Ha, Jawon; Luzi, Giovanni; Sevenich, Robert; Rodríguez Agudo, José; Rauh, Cornelia; Delgado, Antonio (High Pressure Research, 2019)
CO2 gas hydrate technology seems to be a gentle way to concentrate juices, especially comparing to evaporation processes which achieve high levels of concentration and is furthermore energetically favorable in contrast to freeze concentration processes. CO2 can form gas hydrates at around 30–80 bar and 274–283 K. For evaluating this new technology, it is not only important to know the phase equilibrium lines of commercial juices like apple and orange juices but also how the application of e.g. a bubble column affects the gas hydrate formation and separation from the concentrated product. In order to support the experimental outcome, numerical modeling seems suitable to understand the physical background of this novel concentration technology. This includes the simulation of temperature, velocity, pressure and concentration fields using finite volume technique. All three work packages combined will lead to a better understanding of the behavior of gas hydrate technology used to concentrate liquid foo
Keywords: Fruit juice; hydrate technology; food technology; gas hydrate; carbon dioxide/CO2 clathrate; CO2 hydrate

Potential Application of Innovative Gas Hydrate Technology in Fruit Juices Concentration Process - Loekman, Soebiakto; Claßen, Timo; Seidl, Pia; Luzi, Giovanni; Gatternig, Bernhard; Rauh, Cornelia; Delgado, Antonio (Proceedings of 2019 World Congress on Advances in Nano, Bio, Robotics, and Energy, 2019)

Review on the food technological potentials of gas hydrate technology - Claßen, Timo; Seidl, Pia; Loekman, Soebiakto; Rauh, Cornelia; Delgado, Antonio; Gatternig, Bernhard (Current Opinion in Food Science, 2019)
Gas hydrate technology has been known for a long time, but has only recently gained interest in food technology field. A major advantage for food technology applications are the gentle conditions under which products can be refined using gas hydrates, therefor not altering or damaging valuable product contents. This review discusses recent developments of hydrate applications for different areas of food technology for example concentration and purification processes, the preservation of foodstuff as well as novel product designs.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Gashydrate; Lebensmitteltechnologie; Fruchsaftkonzentration

Virtual and experimental studies for establishing an emerging bakery technology with substitution of baking yeast by particulate CO2 hydrates - Mobarak, Mohammad Mobarak; Claßen, Timo; Frühling, Yvonne; Srivastava, Shubhangi; Kollemparembil, Ann Mary; Grill, Bernhard; Zettel, Viktoria; Hitzmann, Bernd; Delgado, Antonio (HPBB2022, 2022)